1979
DOI: 10.1002/ana.410060514
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal choreoathetosis associated with thyrotoxicosis

Abstract: 0364-5 1341791A 35-year-old woman was admitted with complaints of weakness and muscle spasms. Grand ma1 seizures had begun at age I 3 years and responded well to treatment with phenobarbital and phenytoin. At age 26 she had had an episode of status epilepticus, which left her with memory impairment that recovered after several months. Eighteen months prior to admission, dysphagia, diplopia, dysarthria, and generalized weakness developed. Myasthenia gravis was diagnosed o n the basis of response to anticholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…14 Therefore, it was proposed that chorea induced by hyperthyroidism might be linked to increased sensitivity of striatal catecholamine receptors. However, Fischbeck and Layzer, 15 based on their clinical experience, suggested that a pre-existing structural lesion of basal ganglia might be necessary for thyrotoxicosis to induce involuntary movements. Reappearance of BCB, associated with increased serum levels of thyroid hormones and lack of relevant changes on brain CT/MRI scans in our patient, favored the suggestion that the involuntary movements were likely due to thyrotoxicosis-induced biochemical changes, without necessity for the coexistence of a structural lesion or lesions.…”
Section: Discussionmentioning
confidence: 98%
“…14 Therefore, it was proposed that chorea induced by hyperthyroidism might be linked to increased sensitivity of striatal catecholamine receptors. However, Fischbeck and Layzer, 15 based on their clinical experience, suggested that a pre-existing structural lesion of basal ganglia might be necessary for thyrotoxicosis to induce involuntary movements. Reappearance of BCB, associated with increased serum levels of thyroid hormones and lack of relevant changes on brain CT/MRI scans in our patient, favored the suggestion that the involuntary movements were likely due to thyrotoxicosis-induced biochemical changes, without necessity for the coexistence of a structural lesion or lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to dystonias in general [16], primary PxDs tend to be pure movement disorders, whereas secondary PxDs are characteristically associated with baseline neurological symptoms present between paroxysmal episodes, such as mental retardation and epilepsy [4]. These symptomatic PxDs are caused by a wide range of conditions [5], including thyroid disorders [8,10,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…He wrote that true chorea is thought to exist in a few cases in childhood or youth. Early in this century, 20 years after the first report by Gowers thyrotoxicosis was already regarded as one of the important causes of choreic movements, because some other reports (4)(5) had confirmed the relationsip between thyrotoxicosis and chorea. Although hyperthyroidism is not a rare disease, only one case has been reported in the Japanese literature since 1970 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperthyroidism is not a rare disease, only one case has been reported in the Japanese literature since 1970 (2). On the other hand, 14 cases were pub lished in the European and North American literature (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although the precise incidence rate of chorea in hyperthyroidism is obscure, the rarity of Japanese case reports possibly suggests a lower incidence in Japanese than in Caucasian patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation